Mr. Robot. Season_2.0 [videorecording (DVD)] - Slater, Christian; Malek, Rami; Doubleday, Portia (Universal Studios Home Entertainment, 2017)
Winner of the Golden Globe for Best TV Drama, it follows Elliot Alderson, a young cyber-security engineer who becomes involved in the underground hacker group fsociety, after being recruited by their mysterious leader. Following the events of fsociety's 5/9 hack on multi-national company Evil Corp, the second season explores the consequences of that attack as well as the illusion of control.